From the inside out: Ion fluxes at the centre of endocytic traffic. (August 2021) - Chadwick, Sarah R.; Grinstein, Sergio; Freeman, Spencer A.
Abstract: Endocytic traffic is a complex and elegant operation involving cargo sorting, membrane budding and tubulation, generation of force, and the formation of organellar contacts. The role of specific proteins and lipids in these processes has been studied extensively. By comparison, precious little is understood about the contribution of the endocytic fluid to these events, despite much evidence that alteration of the contents can severely affect membrane traffic along the endocytic pathway. In particular, it has long been appreciated that dissipation of ionic gradients arrests endosome-to-lysosome maturation. How cells sense inorganic ions and transmit this information have remained largely enigmatic. Herein, we review the experimental findings that reveal an intimate association between luminal ions, their transport, and endocytic traffic. We then discuss the ionic sensors and the mechanisms proposed to convert ion concentrations into protein-based trafficking events, highlighting the current paucity of convincing explanations.